Internal Migration, Demographic Transition, and Socio-Educational Selectivity in Nepal (Tejganga Darpan, 2026)
The internal migration is transformed into a resettlement-based policy initiative backed by the State into a huge socio-economic process that has great effects on the federal planning and on the development of the regions in Nepal. The paper examines secondary data on the National Population and Housing Census (1981-2021) to identify long-term patterns in how population redistribution, migration motives, and demographic change within Nepal have changed across ecological zones in the country. The results of the analysis based on such indicators as the rate of population growth, the ratio of the efficiency of migration, and the gender-disaggregated factors of the latter can illustrate an intensive demographic transition towards the Tarai region, where 53.6 percent of the total population in the country is now concentrated, and the Mountain region has experienced the first negative growth rate in 2021. Kathmandu Valley has become a key destination for migration, with a net migration rate of 10.5 percent. Other findings of the study include the feminization of internal migration, a decline in agriculture-based mobility, and an increase in education-based and economy-based migration. Such tendencies suggest a change in the rural subsistence-based movement to urban-aspirational mobility, which entails significant implications for gender-sensitive urban planning and balanced regional development in Nepal.